The Experiences of Mature Age Students Transitioning to Higher Education - Boston, Nicholas (Auckland University of Technology, 2017)
This thesis examines mature students’ experiences of transitioning to university. An interpretive, hermeneutic framework is used to guide the interpretation of the experiences of the participants. Twelve mature students from health and education programmes took part in this study. Six were individually interviewed and six were part of a focus group that endeavoured to elicit their experiences as students in a new learning situation. Mature students are a significant cohort within the university student population. Many have not partaken in formal education for a long period of time and face multiple challenges when entering the tertiary setting. Unknown expectations and not being academically prepared for the rigours of student requirements were some issues that could inhibit the transition of these students to the new learning environment. Findings of this study provide insights into what aspects of the transition process assisted the participants’ integration. Characteristics of the mature student such as their life experience and motivation appeared to aid their progress to be part of the university cohort. University structures and practices such as valuing diversity and timetabling played a role in how the non-traditional mature student engaged with their learning. Acknowledgement of the mature student’s situation could perhaps lead to early university interventions that enable students to test their proficiency of their academic skills and become familiar with the requirements at this level.
Keywords: Mature students; Transition; Experience; Higher Education; Student Engagement